Promoting potential through purposeful inclusive assessment for distance learners. Issue 4 (2nd October 2022) - Gibson, Poppy; Clarkson, Rebecca; Scott, Mike
Abstract: The number of students with disabilities, which covers a range of conditions including physical and cognitive impairments, is on the rise. Further and higher education institutions are obliged to ensure that teaching and assessment is inclusive. This is particularly pertinent since the pandemic as many students have missed social opportunities that may have offered academic capital. We conducted a systematic review of relevant United Kingdom literature on how assessment for distance education in further education and higher education can be made inclusive in practical and purposeful ways. Assessment is the fundamental way that we measure students' understanding and progress; it is only through demonstrating knowledge against the set criteria and learning outcomes that students can pass assessments and earn credits toward completion of their degree. We found three key themes in promoting student potential: (a) purposeful and accessible feedback, (b) online group work opportunities, (c) student agency over assessment format.